Fragmentation of cell‐free DNA is induced by upper‐tract urothelial carcinoma–associated systemic inflammation. Issue 1 (12th November 2020) - Nakano, Kosuke; Yamamoto, Yoshiyuki; Yamamichi, Gaku; Yumiba, Satoru; Tomiyama, Eisuke; Matsushita, Makoto; Koh, Yoko; Hayashi, Yujiro; Wang, Cong; Ishizuya, Yu; Kato, Taigo; Hatano, Koji; et al.
Abstract: Reliable biomarkers for upper‐tract urothelial carcinoma (UTUC) have yet to be found. Plasma cell‐free DNA (cfDNA) has been clinically applied as a minimally invasive blood biomarker for various types of cancer. We investigated the utility of plasma cfDNA as a blood biomarker in UTUC patients. The fragment size of plasma cfDNA was shorter and the concentration of plasma cfDNA was higher in UTUC patients than in healthy controls. The fragment size of plasma cfDNA had a moderate accuracy of diagnosing UTUC (area under the curve [AUC] = 0.72), and multivariate analysis indicated that the fragment size of plasma cfDNA was significantly associated with the presence of UTUC (odds ratio = 0.807, 95% confidence interval [CI] 0.653‐0.955, P = .024). Furthermore, we found that the size of plasma cfDNA shortens alongside disease progression ( P < .001). The fragment size of plasma cfDNA in UTUC patients may be an auxiliary tool for the diagnosis of UTUC patients. We also found a high correlation between the fragmentation of plasma cfDNA and serum levels of three inflammatory cytokines (TNFα [ r = −.837], interleukin‐6 [IL‐6] [ r = −.964], interleukin‐1 receptor antagonist [IL‐1ra] [ r = −.911]), which were reported to associate with poor prognosis. Also, we found that the proportion of short fragments of cfDNA was significantly increased in the supernatant of peripheral blood mononuclear cells (PBMCs) from healthy controls cultured in media containing TNFα. These results supposed that cancer‐associated systemic inflammation, especially tumor necrosis factor‐α (TNFα), may contribute to the fragmentation of plasma cfDNA in UTUC patients. Abstract : We found that the fragment size of plasma cell‐free DNA (cfDNA) had moderate accuracy for the diagnosis of upper‐tract urothelial carcinoma (UTUC). We also found that the size of plasma cfDNA shortens alongside disease progression and clarified that the fragmentation of cfDNA was caused by cancer‐related systemic inflammation, especially tumor necrosis factor‐α (TNFα).